Manichaeism and Mandaeism: A Case of Formative Entanglement - Băncilă, Ionuț Daniel (Gnosis, 2025)
Even if the label Gnosticism is contested, it offered a viable ground for a synchronic reading of Manichaean and Mandaean sources, ever since the first Western edition of a major Mandaean text in 1867. This scholarly practice, when pursued on the increasingly solid ground of philological textual analysis, revealed that Manichaean Coptic poetry and Mandaean religious hymnography have much in common. Finally, the discovery of the Greek Mani hagiography further confirmed these findings, diverting the interrogation of the origins of Manichaeism to another fuzzy term: “Jewish-Christianity.” This article argues that, when read together, Manichaean and Mandaean sources offer unique glimpses into the vivid Mesopotamian Aramaic religious koinē before the Islamic takeover of the region. Properly reconstructed from extant Mandaean texts, this common “Gnostic” religious language comprises not only shared mythologoumena, but also historically valuable hints on rituals and geography shared or disputed by different emerging and entangled religious formations.